Eksistensi Badan Permusyawaratan Desa sebagai Mitra Pemerintah Desa - Muh Alfian Fallahiyan; M. Saleh; H. A. Khair (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to enhance the understanding of BPD members regarding the importance of village regulation formulation, strengthen institutional capacity in performing legislative functions, and establish effective partnerships between BPD and the village government. The activity was conducted on July 15, 2025, at the Pringgasela Village Office Hall, involving participants consisting of village officials, chairpersons and members of BPD, and community leaders from various elements. The implementation method applied a participatory approach through socialization, and focus group discussion (FGD). The results indicated an improvement in participants' understanding of the urgency and stages of village regulation formulation as well as the importance of supervisory functions in village governance. This activity contributes to strengthening the existence of BPD as a partner of the village government in achieving participatory and accountable village governance.